The protection of suffrage through legal remedies - Колодін, Денис Олексійович; Колодін, Д. О.; Колодин, Денис Алексеевич; Kolodin, Denys O.; Колодіна, Анна Сергіївна; Колодіна, А. С.; Колодина, Анна Сергеевна; Kolodina, Anna S.; Камінський, Петро Валерійович; Камінський, П. В.; Каминский, Петр Валерьевич; Kaminskyi, Petro V. (Editorial Primmate S. A. S., 2019)
This article is devoted to the issue of the legal protection of citizens' electoral rights. The object of the study is the social relations that arise during the realization by citizens of their electoral rights. The subject of the study is the legal remedies for the protection of the citizens' electoral rights. Moreover, the novelty of this article is that it first attempted to identify the problems of the electoral rights of Ukrainian citizens, and to indicate ways to overcome them. The purpose of the article is a systematic analysis of the electoral rights of citizens, the identification of problems of protection of data rights and the determination of proposals to improve the mechanism of protection of electoral rights of citizens. The key methods of scientific research are general scientific methods of analysis and synthesis, dialectical and logical methods. Specific methods to be used in the study will be: comparative, forensic, and formal legal. In the conclusion the authors highlighted the most promising measures for the protection of citizens' electoral rights and established that there are two main forms of suffrage protection: judicial and extra-judicial.

Cтаттю присвячено дослідженню питання особливостей правового захисту виборчих прав громадян. Об’єктом дослідження є суспільні відносини, які вникають під час реалізації громадянами їх виборчих прав. Предметом дослідження є наявні правові засоби захисту виборчих прав громадян. Новизна цієї статті полягає в тому, що вона визначає проблеми виборчих прав громадян України та вказує шляхи їх подолання. Метою статті є системний аналіз інституту виборчих прав громадян, висвітлення проблем захисту цих прав та надання пропозицій щодо вдосконалення механізму захисту виборчих прав громадян.Основними методами наукового дослідження є загальнонаукові методи аналізу та синтезу, діалектичний та логічний. Спеціально-наукові методи, які будуть використовуватись у дослідженні є: порівняльно-юридичний та формально-правовий. У висновку автори висвітлили найбільш перспективні заходи захисту виборчих прав громадян та встановили, що існує дві основні форми захисту виборчих прав: судовий та позасудовийз їх подальшим обґрунтуванням.
Kolodin D. The protection of suffrage through legal remedies / D. Kolodin, A. Kolodina, P. Kaminskyi // Amazonia Investiga. – Vol. 8. - Issue 22. – Editorial Primmate S. A. S., 2019. – P. 344-349.
Keywords: voting rights; elections; protection of rights; legal remedies; виборчі права; вибори; захист прав; засоби захисту; Research Subject Categories::LAW/JURISPRUDENCE